What is the sum of all integers n that satisfy ∣ ∣ ∣ ∣ n + 2 2 0 ∣ ∣ ∣ ∣ > 5 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Squaring both sides we have ( n + 2 ) 2 4 0 0 > 2 5 or 1 6 > ( n + 2 ) 2 for n = − 2 .
So taking square root on both sides, we have ∣ n + 2 ∣ < 4 for n = − 2 .
If n is non-negative, we have n + 2 < 4 or n < 2 . In this case n can be 0 or 1 .
If n is negative, we have − n − 2 < 4 or n < − 6 for n = − 2 . In this case n can be − 5 , − 4 , − 3 or − 1 .
Therefore sum of all integer values of n is − 5 − 4 − 3 − 1 + 0 + 1 = − 1 2 .
Relevant wiki: Absolute Value Inequalities - Problem Solving
We can make use of the property: ∣ ∣ ∣ y x ∣ ∣ ∣ = ∣ y ∣ ∣ x ∣ if y = 0 . Note that n cannot be − 2 since that that would make the denominator equal to zero.
⟹ ∣ n + 2 ∣ ∣ 2 0 ∣ > 5
We can divide both side of the inequality by the positive number 5.
⟹ ∣ n + 2 ∣ 4 > 1
The fraction is greater than one, if and only if the numerator is greater than the denominator.
⟹ ∣ n + 2 ∣ < 4
⟹ − 4 < n + 2 < 4
⟹ − 6 < n < 2
The integers satisfying this inequality are { − 5 , − 4 , − 3 , − 1 , 0 , 1 } . The sum of these values is − 1 2 □
Problem Loading...
Note Loading...
Set Loading...
∣ ∣ ∣ ∣ n + 2 2 0 ∣ ∣ ∣ ∣ ⟹ ( n + 2 ) 2 4 0 0 ( n + 2 ) 2 n 2 + 4 n − 1 2 ( n + 6 ) ( n − 2 ) > 5 > 2 5 < 1 6 < 0 < 0
Since the inequality is undefined when n = − 2 the acceptable integers n are − 5 , − 4 , − 3 , − 1 , 0 and 1 . And their sum − 5 − 4 − 3 − 1 + 0 + 1 = − 1 2 .